Qualitative Characteristic of Sociability in Groups of Successful and Less Successful Learners of Foreign Languages - G V Zarembo (Peoples' Friendship University of Russia (RUDN University), 2011)
The article deals with a qualitative characteristic of sociability for successful and less successful learners of foreign languages. The statistical estimate showing the differences between average figures on sociability and effectiveness in the second language learning is also given.